Mechanical properties and optimal grain size distribution profile of gradient grained nickel. (July 2018) - Lin, Y.; Pan, J.; Zhou, H.F.; Gao, H.J.; Li, Y.
Abstract: Gradient structured (GS) materials are ubiquitous in biological systems and now increasingly adopted in engineering systems to achieve desirable combinations of mechanical properties. However, how to control and characterize the gradient structure still remains challenging. In the present work, pure Ni samples possessing a gradient structure with a change in the grain size up to three orders of magnitude from 29 nm to 4 μm are prepared by electrodeposition, where the degree of grain size gradient is accurately controlled. The GS Ni samples exhibit a favorable combination of high strength and high ductility. An optimal grain size distribution profile is discovered which gives rise to a yield strength of 460 MPa and a uniform elongation of 8.9%, the latter even better than that of the coarse-grained Ni. Experimental observations and molecular dynamics (MD) simulations reveal that the surface roughening of coarse grains and strain localization of nano-grains can be effectively suppressed by the mutual constraint between nano-grains and coarse grains, leading to the observed superior uniform elongation. This work not only reports a promising methodology of producing materials possessing both high strength and high ductility, but also provides a model for investigating the deformation mechanisms in GS materials. Graphical abstract: Image 1